2022
DOI: 10.3389/fnmol.2022.1068164
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-activated C/EBPβ mediates high-fat diet-induced depression-like behaviors in mice

Abstract: Depression, one of the most common causes of disability, has a high prevalence rate in patients with metabolic syndrome. Type 2 diabetes patients are at an increased risk for depression. However, the molecular mechanism coupling diabetes to depressive disorder remains largely unknown. Here we found that the neuroinflammation, associated with high-fat diet (HFD)-induced diabetes and obesity, activated the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) in hippocampal neurons. This factor represse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (49)(50)(51)(52)(53)(54)(55)(56), depression (57)(58)(59)(60)(61)(62), schizophrenia (63)(64)(65)(66)(67), or epilepsy (68,69), as well as in rodent models of autism (70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (49)(50)(51)(52)(53)(54)(55)(56), depression (57)(58)(59)(60)(61)(62), schizophrenia (63)(64)(65)(66)(67), or epilepsy (68,69), as well as in rodent models of autism (70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (50)(51)(52)(53)(54)(55)(56)(57), depression (58)(59)(60)(61)(62)(63), schizophrenia (64)(65)(66)(67)(68), epilepsy (69,70) and autism (71)(72)(73)(74). Although PLP deficiency is thought to contribute to the respective human conditions (3,75,76), PLP-dependent processes have not yet been considered in the context of 7,8-DHF-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty ZDF rats were randomly divided into the ZDF + Purina group (32% fat, 13% protein, 55% carbohydrate; N = 10) and ZDF + KK group (17.9% fat, 17.5% protein, 48.5% carbohydrate; N = 10) compared with the ZL group (general maintenance diet #1022, N = 10). Behavioral tests, forced swimming test (FST) and open field test (OFT), were, respectively, measured every 2 weeks to evaluate the depressive‐like phenotype 3,26–29 . Gut microbiota composition and metabolome characteristics were measured at the end of this experiment (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Attempts should also be made to elucidate the cellular and tissue-level mechanisms through which these gene products are associated with obesity or depression. Such research would not only place future drug development on a firmer footing, but lead to the elucidation of further novel molecular targets, as well as interactions between those identified in current research [125][126][127][128]. Based on these results, both existing natural and synthetic compounds, as well as "leads" derived from such compounds, could be tested in animal models of obesity with associated depressive-like behaviors or symptoms [129,130].…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 96%